CONCEPTIONS OF BODY AND THE PRACTICE OF PHYSICAL ACTIVITIES: A FOCUS FOR DEFICIENT BODY (Fiep Bulletin - online, 2014)
The present study had as objective analyzes Physical Education - Major Degree of Federal University of Santa Maria/RS academics' conceptions concerning body and deficient body. Open questionnaires were used, applied to forty-two academics of the three semesters of the referred course. For the analysis of these questionnaires, it was used the research of qualitative approach through the analysis of Content of Bardin (1977). The categories of analysis were based in Lüdorf (2003). It was Identified that the body is still being scoped inside of a biological perspective, however, it can be visualized that the course of Physical education is contributing positively in academics' conceptions of body and they were noticed differences among the conceptions of the different semesters, once the academics' conceptions of the most advanced semesters were less linked to biological aspects. It stands out that the way as the body is understood, it interferes directly on the form that this body is treated and worked. Likewise, it intended to focus the subject of the body with physical deficiency, that, inside of a biological perspective it is disabled, it has limitations and difficulties, however, if understood in a more subjective way and inserted into socio-cultural conceptions, this same body starts to be endowed with capacities, with possibilities and spaces inside of all of the areas of the Physical Education. As professionals of an area that works directly with the body, they should to invest, more and more, in subjects that approach this theme, once, there is a need to understand, to accept and to assist in an efficient way all sorts of bodies, independently of their biological marks and then, give the opportunity to everyone to the search of the physical activity in benefit of health and life quality.
Keywords: body conceptions; deficient body; physical education